1984
DOI: 10.1111/j.1476-5381.1984.tb10107.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ryanodine, EGTA and low‐sodium on action potentials in rat and guinea‐pig ventricular myocytes: evidence for two inward currents during the plateau

Abstract: Action potentials were recorded from single cells isolated from rat and guinea‐pig ventricular muscle. In rat cells the repolarization showed two distinct phases, referred to as the early and late phases. In guinea‐pig cells there was a maintained plateau. Reducing external sodium by replacement with lithium or choline suppressed the late phase of the action potential in rat cells, and shortened the plateau of the action potential in guinea‐pig cells. Intracellular EGTA abolished contraction while suppressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
84
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 122 publications
(89 citation statements)
references
References 27 publications
5
84
0
Order By: Relevance
“…The effect of caffeine on the action potential repolarization is not entirely clear. The lack of calcium release during the action potential greatly diminishes the depolarizing Na-Ca exchanger current, therefore, it should shorten the action potential duration in rat ventricular myocardium as it was reported with ryanodine (Mitchell et al, 1984 The reported data with caffeine on the inward calcium current are conflicting. Yatani et al (1984) found that caffeine increased the inward calcium current in rat single ventricular myocytes, but Eisner et al (1979) observed the opposite effect with caffeine on the inward calcium current in sheep cardiac Purkinje fibres.…”
mentioning
confidence: 63%
“…The effect of caffeine on the action potential repolarization is not entirely clear. The lack of calcium release during the action potential greatly diminishes the depolarizing Na-Ca exchanger current, therefore, it should shorten the action potential duration in rat ventricular myocardium as it was reported with ryanodine (Mitchell et al, 1984 The reported data with caffeine on the inward calcium current are conflicting. Yatani et al (1984) found that caffeine increased the inward calcium current in rat single ventricular myocytes, but Eisner et al (1979) observed the opposite effect with caffeine on the inward calcium current in sheep cardiac Purkinje fibres.…”
mentioning
confidence: 63%
“…It is possible that ISi in these cells also contributes to the initiation of the action potential plateau and that, although two phases of the action potential plateau are not visible, another inward current is present to maintain the plateau at a depolarized level. This possibility is considered in detail in the accompanying paper (Mitchell et al, 1984). As seen above, in the presence of strontium, rat action potentials themselves may show only one long plateau, thus obscuring two underlying phases (cf.…”
Section: Discussionmentioning
confidence: 97%
“…Cells were isolated from both ventricles of female DunkinHartley guinea-pigs weighing 400-600g by an enzyme technique (Mitchell et al, 1984) and were layered on a glass coverslip which formed the base of a perfusion chamber situated on …”
Section: Methodsmentioning
confidence: 99%